Push and Pull Factors of Why Medical Students Want to Leave Turkiye: A Countrywide Multicenter Study - Eser, Erhan; Cil, Elif; Sen Gundogan, Nesibe Efruz; Col, Meltem; Ozturk, Elif Nur Yildirim; Thomas, David Terence; Turan, Mustafa (Routledge Journals, Taylor & Francis Ltd, 2024)
Phenomenon: Physician immigration from other countries is increasing as developed countries continue to be desirable destinations for physicians; however, the determinants of Turkish physicians' migration decisions are still unclear. Despite its wide coverage in the media and among physicians in T & uuml;rkiye, and being the subject of much debate, there is insufficient data to justify this attention. With this study, we aimed to investigate the tendency of senior medical students in T & uuml;rkiye to pursue their professional careers abroad and its related factors. Approach: This cross-sectional study involved 9881 senior medical students from 39 different medical schools in T & uuml;rkiye in 2022. Besides participants' migration decision, we evaluated the push and pull factors related to working, social environment and lifestyle in T & uuml;rkiye and abroad, medical school education inadequacy, and personal insufficiencies, as well as the socioeconomic variables that may affect the decision to migrate abroad. The analyses were carried out with a participation rate of at least 50%. Findings: Of the medical students, 70.7% had emigration intentions. Approximately 60% of those want to stay abroad permanently, and 61.5% of them took initiatives such as learning a foreign language abroad (54.5%) and taking relevant exams (18.9%). Those who wanted to work in the field of Research & Development were 1.37 (95% CI: 1.22-1.54) times more likely to emigrate. The push factor that was related to emigration intention was the working conditions in the country (OR: 1.89, 95% CI: 1.56-2.28) whereas the social environment/lifestyle abroad was the mere pull factor for the tendency of emigration (OR: 1.73, 95% CI: 1.45-2.06). In addition, the quality problem in medical schools also had a significant impact on students' decisions (OR: 2.20, 95% CI: 1.83-2.65). Insights: Although the percentage of those who want to emigrate definitely was at the same level as in the other developing countries, the tendency to migrate permanently was higher in T & uuml;rkiye. Improving working conditions in the country and increasing the quality of medical faculties seem vital in preventing the migration of physicians.
Keywords: Medical education; medical students; career choice; immigration; emigration